Gastrointestinal Endometriosis Causing Subacute Intestinal Obstruction with Gradual Development of Weight Loss and Misdiagnosed as Irritable Bowel Syndrome - Amir Soumekh (Case Reports in Gastroenterology, 2014)
Both endometriosis and irritable bowel syndrome (IBS) are commonly found in young women and the diagnosis of either is challenging. Alarm symptoms can exclude the diagnosis of IBS, but their onset may be insidious and often no evidence of organic disease may be found. We present a patient with a 4-year history of presumed IBS, absent gynecological symptoms, negative gastrointestinal as well as gynecological testing who developed the only alarm symptom of weight loss and was eventually found to have endometriosis of the small intestine. This case illustrates the need for constant vigilance in patients with IBS.